2020
DOI: 10.1002/1873-3468.13887
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein L1 is transcriptionally regulated by SP1, IRF1 and IRF2 in hepatoma cells

Abstract: Edited by L aszl o Nagy Apolipoprotein L1 (APOL1) participates in lipid metabolism. Here, we investigate the mechanisms regulating APOL1 gene expression in hepatoma cells. We demonstrate that the À80-nt to +31-nt region of the APOL1 promoter, which contains one SP transcription factor binding GT box and an interferon regulatory factor (IRF) binding ISRE element, maintains the maximum activity. Mutation of the GT box and ISRE element dramatically reduces APOL1 promoter activity. EMSA and chromatin immunoprecipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…We found that APOL1 , APOL2 and APOL6 expression in human beta cells is mediated by the inflammatory JAK–STAT pathway. Other studies have shown that Sp1, IRF1 and IRF2 can bind to the APOL1 promoter in hepatoma cells [ 40 ], and IRF1, IRF2 and STAT2 to the APOL1 promoter in podocytes and endothelial cells [ 17 ]. In addition, the authors of this latter study showed that NF-κB inhibitors downregulate poly(I:C)-induced APOL1 expression, although NF-κB subunits did not bind to the APOL1 promoter directly [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that APOL1 , APOL2 and APOL6 expression in human beta cells is mediated by the inflammatory JAK–STAT pathway. Other studies have shown that Sp1, IRF1 and IRF2 can bind to the APOL1 promoter in hepatoma cells [ 40 ], and IRF1, IRF2 and STAT2 to the APOL1 promoter in podocytes and endothelial cells [ 17 ]. In addition, the authors of this latter study showed that NF-κB inhibitors downregulate poly(I:C)-induced APOL1 expression, although NF-κB subunits did not bind to the APOL1 promoter directly [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…qPCR analysis of APOL1 in RCC 786-O demonstrated a ~200 fold higher expression level than unstimulated immortalized normal podocytes. Interferon Gamma (IFNγ), a strong regulator of APOL1 [12], elevated APOL1 expression both at the mRNA and protein levels in RCC (Figure 1A-C). Immunofluorescence (IF) analysis confirmed high protein levels of APOL1 in RCC compared with immortalized normal podocytes (Figure 1D,E).…”
Section: Apol1 Expression In Rcc 786-omentioning
confidence: 99%
“…The high frequency of G1 and G2 alleles emanated from the protection they confer against African sleeping sickness caused by either Trypanosoma brucei, Trypanosoma gambiense, or Trypanosoma rhodesiense [10,11]. The expression of APOL1 is regulated in a cell-specific mode by specific protein 1 (Sp1) and interferon regulatory factors 1 and 2 (IRF1 and IRF2) [12]. Various roles were proposed for APOL1 proteins, including in autophagy [13][14][15], inflammatory cell death (pyroptosis) [15], impairment of vacuolar acidification [16], ER stress [17], lysosomal membrane permeability [18], mitochondrial dysfunction [19][20][21][22], and cationic channel activity at the plasma membrane [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…One IFN response gene known to be associated with kidney disease is APOL1 , encoding apolipoprotein-L1 (APOL1), a secreted member of a larger family of apolipoproteins known to modulate immune responses. 14 Coding variants in APOL1 common among individuals of recent African ancestry confer a heterozygous advantage against sleeping sickness, but individuals harboring biallelic variants are at increased risk for developing glomerular disease. 15 , 16 This appears to be triggered by conditions such as HIV, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), hypertension, and lupus, 17 , 18 each of which is associated with chronic systemic inflammation and a sustained increase in IFN gene expression.…”
Section: Introductionmentioning
confidence: 99%